Le symbolisme phonétique et la fonction iconique de l’analogie (Signifiances (Signifying), 2020)
The definition of sound symbolism is fluctuating and sometimes confusing. This paper, after showing the growing interest in this type of linguistic phenomenon which nevertheless remains fringe, proposes a critical analysis of the very frequently cited typology of Hinton, Nichols and Ohala (1994), then of the treatment of the question from the perspective of iconicity and, finally, from an analogical perspective. A definition of the prototype of sound symbolism is proposed as a phonosemantic analogy, an analogy that has three characteristics: it involves a phonic element, it is binary and heterogeneous.